2020
DOI: 10.1177/1362361320909176
|View full text |Cite
|
Sign up to set email alerts
|

How accurate are autistic adults and those high in autistic traits at making face-to-face line-of-sight judgements?

Abstract: Being able to follow the direction of another person’s line-of-sight facilitates social communication. To date, much research on the processes involved in social communication has been conducted using computer-based tasks that lack ecological validity. The current paradigm assesses how accurately participants can follow a social partner’s line-of-sight in a face-to-face scenario. In Study 1, autistic and neurotypical adults were asked to identify which location, on a grid of 36 potential locations, the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Some studies report little evidence of differences in the frequency or accuracy of looks to social stimuli (191) inviting the conclusion that social attention is typical in older individuals. However, other studies suggest that social attention remains less efficient or more effortful in older individuals with ASD (156,(192)(193)(194); Liu et al, (in submission). Indeed, one recent study suggests that adolescents with ASD may display less efficient covert processing of eye contact (195).…”
Section: Motivation and Social Attention In Older Individualsmentioning
confidence: 99%
“…Some studies report little evidence of differences in the frequency or accuracy of looks to social stimuli (191) inviting the conclusion that social attention is typical in older individuals. However, other studies suggest that social attention remains less efficient or more effortful in older individuals with ASD (156,(192)(193)(194); Liu et al, (in submission). Indeed, one recent study suggests that adolescents with ASD may display less efficient covert processing of eye contact (195).…”
Section: Motivation and Social Attention In Older Individualsmentioning
confidence: 99%
“…For example, we recently conducted a face-to-face gaze following task where participants were asked to point to the exact location of an experimenter's gaze across a series of carefully paced and timed trials. We observed that both autistic and non-autistic adults were able to effectively follow an experimenter's gaze direction following both long looks and brief glances, though performance of autistic individuals was overall less accurate than neurotypicals [ 46 ]. It is possible that the suggestion that some autistic individuals find direct eye-contact aversive [ 47 , 48 ] may lead to reduced experience with direct eye-contact, and therefore fewer opportunities to practice gaze following in real-life situations.…”
Section: The Face-to-face Encounter and Autismmentioning
confidence: 99%
“…It is clearly the case, though, that measures of social attention are a significant part of the reliable operational diagnostic definition of the preschool phenotype of autism (Mundy & Bullen, 2022). Moreover, beyond the preschool period, social attention can also be reliably and validly measured in children, adolescents and adults with typical development and autism (e.g., Bayliss et al, 2013; Freeth et al, 2020; Freeth & Bugembe, 2019; Gregory & Kessler, 2022; Grynszpan et al, 2019; Mundy et al, 2016; Nowell et al, 2020; Oberwelland et al, 2016), as well as among individuals who exhibit the broad autism phenotype (Elsabbagh et al, 2009; Morgan et al, 2023; Nayar et al, 2022; Swanson et al, 2013; Swanson & Siller, 2014; Zhao et al, 2017). Recent research also suggests that social attention measures may be sensitive to sex differences in autism (Charwarska et al, 2016; Harrop et al, 2020).…”
Section: The Hypothetical Construct Of Social Attention In Autism Res...mentioning
confidence: 99%
“…Latency measures can be used to assess the effort associated with social attention/joint attention (Gredebäck et al, 2010; Oberwelland et al, 2016; Vaughn Van Hecke et al, 2012). This is notable because research suggests that social‐attention may remain less efficient or more effortful in older autistic individuals and those who exhibit the broad autism phenotype (Birmingham et al, 2017; Freeth et al, 2020), as well as in social interactions involving higher perceptual or cognitive load (Haskins et al, 2022; Hernandez et al, 2020). Thus, with development children and adults with autism may be better able to engage in social attention, but this may require greater effort which taxes the adaptive and effective use of social attention in social communication or didactic learning interactions (Mundy & Bullen, 2022).…”
Section: The Hypothetical Construct Of Social Attention In Autism Res...mentioning
confidence: 99%